CFD Simulation and Optimization of Very Low Head Axial Flow Turbine Runner - Yohannis Mitiku Tobo; A. Venkata Ramayya; Getachew Shunki Tibba (International Journal of Renewable Energy Development, 2015)
The main objective of this work is Computational Fluid Dynamics (CFD) modelling, simulation and optimization of very low head axial flow turbine runner  to be used to drive  a centrifugal pump of turbine-driven pump. The ultimate goal of the optimization is to produce a power of 1kW at head less than 1m from flowing  river to drive centrifugal pump using mechanical coupling (speed multiplier gear) directly. Flow rate, blade numbers, turbine rotational speed, inlet angle are parameters used in CFD modeling,  simulation and design optimization of the turbine runner. The computed results show that power developed by a turbine runner increases with increasing flow rate. Pressure inside the turbine runner increases with flow rate but, runner efficiency increases for some flow rate and almost constant thereafter. Efficiency and power developed by a runner drops quickly if turbine speed increases due to higher pressure losses and conversion of pressure energy to kinetic energy inside the runner. Increasing blade number increases power developed but, efficiency does not increase always. Efficiency increases for some blade number and drops down due to the fact that  change in direction of the relative flow vector at the runner exit, which decreases the net rotational momentum and increases the axial flow velocity.